(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The abstract of the "Strategic Analysis of the Tourism Market in Uzbekistan" would provide a brief summary of the research paper’s main points, findings, and conclusions regarding the tourism market in Uzbekistan. This would include information on the current state of the tourism market, the strategies being implemented to promote tourism in the country, and the potential for further growth and development in the future.